2020
DOI: 10.1002/jcp.29529
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of cell autophagy and apoptosis in cervical cancer by inhibition of long noncoding RNA LINC00511 via transcription factor RXRA‐regulated PLD1

Abstract: An increasing number of studies have explored the relationship of long noncoding RNAs (lncRNAs) with cervical cancer, yet the role of LINC00511 in cervical cancer still remains elusive. The current dissertation was intended to explore the effect of LINC00511 on cervical cancer development by regulating phospholipase D1 (PLD1) expression through transcription factor retinoic X receptor alpha (RXRA). Differentially expressed lncRNA and messenger RNA related to cervical cancer were screened by microarray-based ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 23 publications
3
29
0
Order By: Relevance
“…Shi et al reveal that LINC00511 regulates the expression of PLD1 via accumulation of transcription factor RXRA in the promoter region of the PLD1 in HeLa cells. 23 In the present study, we confirmed that LINC00511 was mostly expressed in the cytoplasm of cervical cancer cells, which may function as a ceRNA. LINC00511 is also reported to amass in cytoplasm in gastric cancer 29 and pancreatic adenocarcinoma cells.…”
Section: Dovepresssupporting
confidence: 82%
See 2 more Smart Citations
“…Shi et al reveal that LINC00511 regulates the expression of PLD1 via accumulation of transcription factor RXRA in the promoter region of the PLD1 in HeLa cells. 23 In the present study, we confirmed that LINC00511 was mostly expressed in the cytoplasm of cervical cancer cells, which may function as a ceRNA. LINC00511 is also reported to amass in cytoplasm in gastric cancer 29 and pancreatic adenocarcinoma cells.…”
Section: Dovepresssupporting
confidence: 82%
“…16 Previous studies have revealed that LINC00511 is also up-regulated in cervical cancer and associated with poor prognosis, and serves as an oncogene gene in HPV-positive cervical cancer cells. 20,23 Herein, what we have in common with previous research was that LINC00511 was significantly up-regulated in cervical cancer and promoted tumor development. In addition, this study revealed, for the first time, the promoting effect of LINC00511 on HPV-negative cervical cancer cells.…”
Section: Dovepresssupporting
confidence: 57%
See 1 more Smart Citation
“…RXRa is a member of the nuclear receptor (NR) superfamily, which functions in the regulation of transcription, and in controlling the development, homeostasis, and metabolism of organisms (53). RXRa is downregulated in cervical cancer and inhibits its progression (54). In this study, proteomics analysis and bioinformatics prediction showed that the ITCH promoter contains a DNA binding site for RXRa, and ITCH and RXRa were consistently upregulated.…”
Section: Discussionmentioning
confidence: 69%
“…In cervical cancer, inhibition of LINC00511 was found to promote cell apoptosis and autophagy via RXRA-regulated PLD1. 21 In hepatocellular carcinoma, overexpression of LINC00511 was correlated with poor prognosis, and promoted cell metastasis and proliferation by regulating of miR-424. 22 LINC00511 functioned as a competing endogenous RNA to regulate VEGFA via sponging miR-29b-3p in pancreatic ductal adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%